Complete IELTS. - Brook-Hart, Guy (Cambridge University Press, 2012)
This book consists of the Student's Book without answers with CD-ROM which contain all the material for the listening activities. It 10 topic-based units which contains speaking activities. The CD-ROM contains skills, grammar, vocabulary and listening exercises.